Use of information resource facilities and services at PTAR Melaka City Campus during the COVID-19 pandemic: the experience of an academic library / Siti Haidah Md Aziz ... [et al.] - Md Aziz, Siti Haidah; Husaini, Haslinda; Mohamed Shuhidan, Shamila; Jaafa, Ahmad Nazri; Mat Rosli, Mohd Hilmi (Faculty of Information Management, 2024)
The COVID-19 epidemic influenced the student population of the PTAR li-brary on the City Campus of Melaka in a number of ways, one of which was a change in the frequency and volume with which students utilised the campus's information resources. During and after the COVID-19 pandemic, the experiences of one of the University Library branches at UiTM were detailed in this article. Because of the widespread disruption to traditional classroom settings caused by the COVID-19 pandemic, the use of online courses backed by electronic libraries has become increasingly popular. The purpose of this study is to evaluate the use of physical and digital learning materials, as well as customer satisfaction, in a PTAR library prior to and during the COVID19 epidemic. Applications, printed materials, documents, and films were the least-used media due to the constraints of working or studying from home, insufficient infrastructure, a lack of working space, and data subscrip-tions or wifi libraries. The global epidemic was considered to have both posi-tive and negative repercussions for academic libraries. It was suggested that the pattern, concept, and styles of modern information resources and facilities be expanded, that the library capitalise on its many open access re-sources, open data, open educational materials, open services, and open re-pository, and that the library acquire electronic devices immediately. This study aims to evaluate the pattern and scope of use of information resource facilities and services at PTAR Melaka City Campus, as well as the use of the digital library platform at the UiTM Melaka City Campus library.